Disney and Disability: Media Representations of Disability in Disney and Pixar Animated Films - Holcomb, Jeanne; Latham-Mintus, Kenzie (Disability Studies Quarterly, 2022)
Since the merger of Walt Disney Animation Studios and Pixar Animation Studios, Disney has been lauded for creating more progressive content that includes representations of main characters from diverse backgrounds. However, progressive representations of disability (both physical and mental disability) have been slow to emerge in most mediums. The objective of this research is to examine whether portrayals of illness and disability in recent animated feature films produced by Walt Disney Animation Studios or Pixar Animation Studios depict progressive (or multicultural) narratives of disability versus traditional narratives of disability. We analyzed 20 of the most recent (i.e., 2008-2018) animated films from both studios with 9 films from Walt Disney Animation and 11 films from Pixar Animation Studios. Using thematic content analysis, a combination of pre-identified and emergent disability- and illness-related themes are described. Overwhelmingly, disability portrayals were traditional, with disability used to elicit pity or humor from the viewer and to indicate that characters were evil or old. Out of the 20 films, few progressive portrayals of disability were observed. Although Disney has been lauded for being more inclusive in their representations of characters, disability representations continue to perpetuate and reaffirm the stigmatization of disability.